CEO Promotion as A Tool for Internet Marketing - Salimov Fayoz; Narkulova Shakhnoza Shakarbekovna (Genius Journals, 2022)
The relevance of this research topic is due to the fact that at the present time of crisis, business is in dire need of the cheapest and most effective promotion tools, one of which is seo. Research problem: today in Internet marketing there are a large number of promotion tools that allow a business to choose a set of tools suitable for each niche. Also, most of the tools allow you to draw up an accurate portrait of the target audience and show ads only to potential customers, and not to everyone in a row, as is the case, for example, on television. However, not all tools give results immediately, but at the same time they have a high price. In response to this problem, our research suggests examining one of the cheapest and most effective Internet marketing tools - search engine optimization. Purpose: the purpose of the study was to study the features of the application of the seo-optimization method. The research results were obtained using such cognitive methods as abstraction, synthesis, analysis, induction, deduction. Results: site search engine optimization is a fairly effective method of internet marketing. Search engine optimization of the site will bring new customers to companies and, as a result, profits from product sales as long as people do not stop using search engines.
Keywords: Seo; seo-optimization; search engine promotion; website